Harnessing cell cycle intervention and evading P-glycoprotein efflux: natural product-inspired C2-aminophenyl chromones as dual modulators against multidrug-resistant cancer - Chang, Yi-Han; Wu, I-Ting; Chien, Po-Yu; Su, Ching-Hui; Chen, Yu-Hsun; Hung, Chin-Chuan; Hung, Hsin-Yi (European journal of medicinal chemistry, 2025)
The resilience of cancer cells to current anti-neoplastic agents remains a significant challenge in oncology, underscoring the pressing requirement for novel candidates to overcome multidrug-resistant (MDR) malignancies. Building on the C2-functionalized chromone scaffold, herein, a structure-activity relationship (SAR) investigation centered on the C2-atomic bridge identified C2-aminophenyl chromone as a privileged scaffold for tumoricidal compounds. Within this chemotype, 12m and 12n emerged as promising candidates, exhibiting potent anti-proliferative activity against not only drug-sensitive KB cells (IC50 = 0.78 μM and 0.42 μM, respectively) but also MDR KBvin cells (IC50 = 0.69 μM and 0.43 μM, respectively). Mechanistic investigations revealed that both molecules effectively triggered apoptosis and hampered cell cycle transition at the G2/M stage, marked by the upregulation of cyclin B1 and cyclin A2. Moreover, 12m and 12n demonstrated collateral sensitivity and chemosynerstic interactions in MDR cancer cells, significantly suppressing P-glycoprotein (P-gp) expression while bypassing P-gp-mediated efflux. In vivo evaluations using a zebrafish xenograft model further validated their therapeutic potential in terms of KBvin tumor growth without eliciting acute toxicity at 1.0 μM. Harnessing chemoresensitizing properties, these molecules further reduced KBvin tumor burden in zebrafish when co-administered with paclitaxel. To encapsulate, the C2-aminophenyl chromone scaffold represents a novel chemical framework for the development of dual-functional anti-neoplastic agents targeting MDR cancer.
Gesehen am 08.12.2025